2018
DOI: 10.1111/jpm.12448
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of mental health nursing staff working with voice hearers in an acute setting: An interpretive phenomenological approach

Abstract: Introduction Mental health nursing (MHN) staff in acute settings work with voice hearers at times of crises when they experience high levels of distress. Previous research has focused on community mental health staff's experiences and their service users views on exploring the content of voices. No studies have explored this from an acute mental health service perspective. Aim This study therefore sought to explore the experiences of staff working with voice hearers in an acute mental health service. Method Du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(34 citation statements)
references
References 22 publications
(20 reference statements)
3
31
0
Order By: Relevance
“…The first theme examined the practitioner role in starting a conversation about voices. This was not always a straightforward process due to the previously reported barriers experienced by service users (Bogen‐Johnston, de Visser, et al, ) and practitioners (Coffey & Hewitt, ; McMullan et al, ). Our findings suggested that even within a specialist service for the treatment of psychotic experiences, practitioners may not always feel comfortable about having these conversations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The first theme examined the practitioner role in starting a conversation about voices. This was not always a straightforward process due to the previously reported barriers experienced by service users (Bogen‐Johnston, de Visser, et al, ) and practitioners (Coffey & Hewitt, ; McMullan et al, ). Our findings suggested that even within a specialist service for the treatment of psychotic experiences, practitioners may not always feel comfortable about having these conversations.…”
Section: Discussionmentioning
confidence: 99%
“…The current literature suggests that many service users with a diagnosis of psychosis have limited access to formal therapeutic conversations about voice hearing experiences that are consistent with the evidence base (RCP, ). Therefore, the availability of informal conversations can play an important role in bridging the all‐or‐nothing gap, yet barriers to such conversations exist for service users (Bogen‐Johnston, de Visser, et al, ) and practitioners (Coffey & Hewitt, ; McMullan et al, ). This study extends our understanding of these barriers from the perspectives of practitioners working in an EIP Service where these informal conversations are expected to occur (NICE, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stenhouse's (2009Stenhouse's ( , 2011) study revealed service users' unfulfilled expectations of being able to talk with nurses, which mirrored participants' accounts in our study. It is reported that the limited interactions that occur between mental health nurses and service users on acute admission units are seldom therapeutic or theoretically informed (Cameron et al, 2005;McMullan, Gupta & Collins, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Mental health nurses certainly seem to be obligated to administer elements of the system rather than ensuring time is spent with people using services (Simpson, 2005). Nursing staff are reported to experience stress in acute environments that goes beyond concerns about capability and resources to encompass feelings of being ineffective (McMullan et al, 2018). According to Lee, Daffern, Ogloff and Martin (2015), higher levels of stress relating to organizational and staffing issues frequently leave nurses feeling dejected and unvalued.…”
Section: Discussionmentioning
confidence: 99%